Strategist librarian on social media: conceptual approach and possibilities of digital marketing in public libraries - Neves, Barbara Coelho (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2019)
his article has as its theme the librarian social media strategist, considering aspects of digital marketing for sociodigital inclusion in public libraries. It presents some elements of an ongoing research that has as a starting question to know how the public library has been developing strategies for sociodigial inclusion, through the introduction of social media, considering aspects of digital marketing. The general objective is to investigate aspects and possibilities of a strategist librarian on digital social media as a contemporary element of sociodigial inclusion. This research is exploratory and descriptive, with a qualitative and quantitative approach, and a methodology of multiple case studies with the application of digital social network and bibliographical evaluation method. The results present the first stage of the complete study, which is underway. In this way, it highlights the essential aspects to approach digital marketing in public libraries and the proposition of the concept that addresses the potential of strategist librarians on digital social media. At the end, it considers relevant, in the field of Librarianship and Information Science, as the new discussion concept, the strategist librarian serving as an inspiration for broadening the debate on the theme that articulates digital marketing as a subsidy for the development of public policies of information for sociodigital inclusion in public libraries. Key-words: Strategist librarian - concept elaboration. Digital marketing. Digital social media. Communication and Information Processing. Sociodigital inclusion. Public library - Brazil and Europe. Link: http://www.periodicos.ufpb.br/ojs2/index.php/ies/article/view/39203